Attribution of Stratospheric and Tropospheric Ozone Changes Between 1850 and 2014 in CMIP6 Models. Issue 16 (16th August 2022) - Zeng, Guang; Morgenstern, Olaf; Williams, Jonny H. T.; O'Connor, Fiona M.; Griffiths, Paul T.; Keeble, James; Deushi, Makoto; Horowitz, Larry W.; Naik, Vaishali; Emmons, Louisa K.; Abraham, N. Luke; Archibald, Alexander T.; et al.
Abstract: We quantify the impacts of halogenated ozone‐depleting substances (ODSs), greenhouse gases (GHGs), and short‐lived ozone precursors on ozone changes between 1850 and 2014 using single‐forcing perturbation simulations from several Earth system models with interactive chemistry participating in the Coupled Model Intercomparison Project Aerosol and Chemistry Model Intercomparison Project. We present the responses of ozone to individual forcings and an attribution of changes in ozone columns and vertically resolved stratospheric and tropospheric ozone to these forcings. We find that whilst substantial ODS‐induced ozone loss dominates the stratospheric ozone changes since the 1970s, in agreement with previous studies, increases in tropospheric ozone due to increases in short‐lived ozone precursors and methane since the 1950s make increasingly important contributions to total column ozone (TCO) changes. Increases in methane also lead to substantial extra‐tropical stratospheric ozone increases. Impacts of nitrous oxide and carbon dioxide on stratospheric ozone are significant but their impacts on TCO are small overall due to several opposing factors and are also associated with large dynamical variability. The multi‐model mean (MMM) results show a clear change in the stratospheric ozone trends after 2000 due to now declining ODSs, but the trends are generally not significantly positive, except in the extra‐tropical upper stratosphere, due to relatively small changes in forcing over this period combined with large model uncertainty. Although the MMM ozone compares well with the observations, the inter‐model differences are large primarily due to the large differences in the models' representation of ODS‐induced ozone depletion. Plain Language Summary: Overhead ozone absorbs harmful solar ultraviolet light, protecting life on Earth. Due to human activities since the nineteenth century, emissions of greenhouse gases (GHGs) and ozone‐depleting substances (ODSs) containing chlorine and bromine have profoundly affected stratospheric ozone. Near the Earth' surface, ozone has increased substantially leading to worsening air quality. In this study, we use Earth system models to interactively assess the roles of ODSs, ozone‐forming pollutants, and GHGs including methane, carbon dioxide (CO2 ), and nitrous oxide (N2 O) on ozone changes from the surface to the upper stratosphere. Whilst substantial reductions in stratospheric ozone due to ODSs occurred since the 1970s, the lower‐atmospheric ozone increases due to anthropogenic pollution have counteracted this decrease. Increases in GHGs lead to various positive and negative effects on stratospheric ozone in different regions, and their impacts vary with ODS levels in the atmosphere. Amongst the GHGs assessed here, the increase in methane leads to overwhelming positive trends in both stratospheric and tropospheric ozone through mainly chemical effects. The impact of changes in N2 O and CO2 on total column ozone is more uncertain due to large inter‐model differences, although their overall impact is small during the simulation period. Key Points: New multi‐model results show significant positive effects of ozone precursors on near‐global ozone offsetting the negative effects of ozone‐depleting substances (ODSs) ODS and greenhouse gases dominate stratospheric ozone changes but with large inter‐model differences due to uncertainties in responses to ODS changes Increases in carbon dioxide and nitrous oxide significantly impact stratospheric ozone, but their net effects on total columns are small due to cancellations